2008
DOI: 10.1094/pdis-92-2-0234
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Two Little Cherry Viruses in Sweet Cherry in Washington State

Abstract: Little cherry disease, one of the major viral diseases of sweet cherry (Prunus avium) worldwide, is associated with either of two closteroviruses, Little cherry virus 1 (LChV-1) and Little cherry virus 2 (LChV-2). Two sets of primers corresponding to a portion of the replicase gene of LChV-1 and LChV-2 were used in one-tube reverse-transcription polymerase chain reactions to detect these viruses in total RNA extracts of field-collected sweet cherry tissues. LChV-1 and LChV-2 were detected both alone and in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 26 publications
0
13
0
13
Order By: Relevance
“…To determine the most suitable primer pair for the accurate detection of all isolates of LChV1, detection primer pairs reported in the literature were retrieved and compared with all available full-length genomic sequences ( Figure 5 ). In most cases, these detection primers showed either multiple mismatches with some isolates (up to 10–12 mismatches for the 6 for primer of Matic et al [ 2 ]) or mismatches affecting the two 3′-most nucleotides of the primer (in particular the LCUW7090 primer of Bajet et al [ 22 ]). Such mismatches are highly likely to either preclude amplification of some isolates or severely affect the sensitivity of detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the most suitable primer pair for the accurate detection of all isolates of LChV1, detection primer pairs reported in the literature were retrieved and compared with all available full-length genomic sequences ( Figure 5 ). In most cases, these detection primers showed either multiple mismatches with some isolates (up to 10–12 mismatches for the 6 for primer of Matic et al [ 2 ]) or mismatches affecting the two 3′-most nucleotides of the primer (in particular the LCUW7090 primer of Bajet et al [ 22 ]). Such mismatches are highly likely to either preclude amplification of some isolates or severely affect the sensitivity of detection.…”
Section: Resultsmentioning
confidence: 99%
“…Although growing evidence suggests that LChV1 isolates could be largely latent in many of their hosts it is still included in many certification and quarantine schemes and several LChV1 isolates have been tentatively associated with specific syndromes in sweet cherry and in other Prunus species [ 2 , 3 , 22 ]. Regarding the isolates analyzed in the present study, no clear conclusions can be drawn concerning their pathogenicity because as is very frequently the case the trees hosting them were co-infected with several viruses including in some cases different LChV1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far the molecular variability of LChV-1 has been barely studied, with most of the past efforts focusing on short fragments of the RdRp, the CPm and the 3 0 end of ORF8 (Bajet et al, 2008;Matic et al, 2009;Candresse et al, 2013). Phylogenetic relationships between LChV-1 isolates obtained from remote geographical regions and/ or originating from different Prunus trees have shown that classification according to geographic origin or host is probably not feasible (Matic et al, 2009;Candresse et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, the presence of its distinct variants has been connected with other disorders such as Kwanzan stunting [ 35 ] and Shirofugen stunt disease [ 36 ]. Infection of cherry by LChV-1 has been reported all over the world [ 37 , 38 , 39 , 40 ], usually as a coinfection with CVA. Moreover, its presence was also reported from different hosts (almond, peach and plum) [ 35 , 41 ] and recently from apricot [ 17 ].…”
Section: Introductionmentioning
confidence: 99%